The Behavioral Analysis of Media Social Utilization and Its Implications on the Adolescent Based on an Islamic Perspective - Nafisah, Syifaun (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
Social media users show a number that continues to grow. The use of social media has both positive and negative impacts. According to various studies, social media can affect mental health for long-term use. For this reason, research on the effects that arise due to the use of social media needs to be carried out continuously to minimize the harmful effects of using this media. This study aims to determine the impact of social media on changes in adolescent behavior. This study analyzes changes in adolescent behavior based on patterns of access to information. Furthermore, this study investigates the practice of adolescents in accessing and using information sources using Burhuss Skinner's theory and Social Islamic perspective. The results showed that adolescents tend to imitate behavior or Tasyabbuh. If it is not balanced with adequate literacy skills, changes in adolescent behavior have a destructive tendency. Study results show this harmful effect, which offers a negative correlation. Assistance and improvement of adolescent literacy competence will help adolescents reduce the adverse effects of using technology.